Quantifying Water Footprints in Selected Barangays of Sofronio Española, Palawan: Advancing Watershed Conservation and Management - Jabagat, Vanessa C. (Future Science / FSH-PH Publications, 2025)
This study examines the water footprint and watershed man-agement practices in Sofronio Española, Palawan, focusing on sus-tainability, conservation, and efficient resource use. Using a mixed-method approach, the research combines quantitative and qualitative analyses to assess water resource conditions, con-sumption trends, and environmental impacts within the Pulot Wa-tershed.The primary objectives are to evaluate water supply compo-nents, water footprints, and resource conditions, understanding the broader environmental consequences, with the goal of promot-ing sustainable water management strategies.Quantitative data were collected through household surveys with metered water connections using stratified sampling, along-side secondary data from water system records. These data were analysed using trend analysis, forecasting models, and GIS-based spatial mapping. Qualitative data from interviews with key in-formants provided insights into local perspectives on water con-servation, management challenges, and the effectiveness of poli-cies.The findings reveal that rapid population growth, deforesta-tion, and land-use changes due to agriculture, mining, and urbani-zation are significantly impacting the Pulot Watershed. These is-sues, compounded by slash-and-burn farming and inadequate wa-ter management, are contributing to environmental degradation and jeopardizing the watershed’s ability to meet growing water demands. The study highlights critical gaps in governance, public awareness, and stakeholder involvement, emphasizing the need for integrated water resource management.Key recommendations include addressing population growth, improving water management systems, enhancing infrastructure, promoting community participation, and implementing pollution control measures and habitat restoration. These actions align with Sustainable Development Goal 6 (Clean Water and Sanitation) and aim to ensure the long-term health and sustainability of the water-shed.